Coaxially Fabricated Dual‐Drug Loading Electrospinning Fibrous Mat with Programmed Releasing Behavior to Boost Vascularized Bone Regeneration (Adv. Healthcare Mater. 16/2022). Issue 16 (17th August 2022) - Cui, Jinjie; Yu, Xingge; Yu, Bin; Yang, Xiuyi; Fu, Zeyu; Wan, Jianyu; Zhu, Min; Wang, Xudong; Lin, Kaili
Abstract : Controlled Drug Release In article 2200571, Min Zhu, Xudong Wang, Kaili Lin and co‐workers fabricate a novel dual‐drug loading coaxially electrospinning fibrous mat with programmed release behavior. The early and rapid release of angiogenesis‐promoting drug deferoxamine promotes the angiogenesis of vascular endothelial cells and the sustained release of osteogenesis‐inducing drug dexamethasone enhances osteogenesis of bone mesenchymal stem cells, and synergistically boosts vascularized bone regeneration.